(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2023)
This paper examines the economic implications of the Second World War on the Nigerian economy. The focus of the paper is to examine the extent to which the colonial policies put in place during and after the Second World War had impacted on the Nigerian economy. The paper investigated the effects of the colonial policies on the welfare of the Nigerian farmers on one hand and the production of crops on the other. The study of the Second World War period is important because it enables us to examine two crucial elements in the economic history of Nigeria. On the one hand is the pursuit of the economic interest of the colonizing power, and on the other hand is the attendant economic implications of the agricultural policies on both the producers and the general economic landscape of Nigeria. The research work obtained its data from both primary and secondary sources. The primary source consists of archival materials such as Agricultural Department reports, Intelligence Reports, Government Publications and Agricultural Policy documents. The secondary sources for this work were obtained from the earliest Nigerian Newspapers and magazines, relevant textbooks, Journal articles and conference proceedings. The study finds out that the war time colonial agricultural policies rather than alleviating the suffering of the peasant farmers did upset the indigenous economy and made no attempt at improving the agricultural techniques. Furthermore, the farmers were put at disadvantage and short changed through the agency of the marketing boards as they did not receive commensurate price for their agricultural products.